A 46-Year-Old Woman With Dyspnea From an Inhalational Exposure, Triggering Thyroid Storm and Subsequent Multi-Organ System Failure. (December 2015) - Moraco, Andrew H.; Banauch, Gisela; Kopec, Scott
Background: Thyroid storm is a rare, life-threatening condition which arises in patients with thyrotoxicosis, with an annual incidence of 2 patients per 1, 000, 000 and a mortality rate of 11%. Case: We present the case of a 46-year-old-female with a medical history of controlled mild intermittent asthma, who presented with a severe asthma exacerbation, that triggered thyroid storm after exposure to polyurethane fumes. Conclusion: This patient represents, to the best of our knowledge, the first patient in whom the stress related to a severe asthma attack triggered the development of thyroid storm. She also is the first patient with no indication of cardiac dysfunction who developed fatal cardiac arrest after initiation of b-blockade for treatment of thyroid storm.